2019
DOI: 10.7717/peerj.6501
|View full text |Cite
|
Sign up to set email alerts
|

Tumor mutational profile of triple negative breast cancer patients in Thailand revealed distinctive genetic alteration in chromatin remodeling gene

Abstract: Background Triple negative breast cancer (TNBC) is a breast cancer subtype characterized by absence of both hormonal receptors and human epithelial growth factor receptor 2 (HER2). TNBC accounts for 15–20% of breast cancer. TNBC is associated with more aggressive disease and worse clinical outcome. Though the underlying mechanism of TNBC is currently unclear, the heterogeneity of clinical characteristics in various population may relate to the difference in tumor mutational profile. There were studies on TNBC … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
21
2
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(27 citation statements)
references
References 40 publications
3
21
2
1
Order By: Relevance
“…In a South Korean cohort of 229 patients with ER+ and Her2-breast cancer, TP53 was found mutated in 10% of the patients [19], compared to 16.7% in 'luminal A and luminal B/Her2-combined' in our cohort. In a study of 116 triple-negative patients from Thailand [20], 76% were found to carry TP53 mutations, comparing to 92% in the same subtype in our cohort. Recapitulating, the high prevalence of mutations in TP53 implies a distinct molecular characteristic of EOBC and associated subtypes.…”
Section: Discussioncontrasting
confidence: 50%
“…In a South Korean cohort of 229 patients with ER+ and Her2-breast cancer, TP53 was found mutated in 10% of the patients [19], compared to 16.7% in 'luminal A and luminal B/Her2-combined' in our cohort. In a study of 116 triple-negative patients from Thailand [20], 76% were found to carry TP53 mutations, comparing to 92% in the same subtype in our cohort. Recapitulating, the high prevalence of mutations in TP53 implies a distinct molecular characteristic of EOBC and associated subtypes.…”
Section: Discussioncontrasting
confidence: 50%
“…TNBC represents a heterogeneous subtype of breast cancer with adverse clinical outcomes and inconsistent responses to current therapy, particularly in advanced-stage disease [3,4,8]. Data from previous studies revealed that the spectrum of mutation profiles is diverse between each patient and also differs amongst racial and ethnic groups [10,17,18,27,28]. Although there are multiple explanations for the diverse genomic landscape of TNBC patients, ethnicity could have a significant role in this discrepancy.…”
Section: Discussionmentioning
confidence: 99%
“…TP53 is widely considered to be a guardian of the genome because of its critical function in maintaining genome integrity, regulating the cell cycle, and initiating apoptosis. Multiple studies reported the frequency of TP53 mutation in human breast cancer ranged from 50% to 82% [17][18][19][20][21].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…patients. Non-synonymous and synonymous variants were included in this calculation, synonymous mutations were considerd purposefully to reduce sampling noise [36].…”
Section: Variant Allele Frequencies Changes (Dvaf) Calculationmentioning
confidence: 99%